MAGNDATA: towards a database of magnetic structures. I. The commensurate case. Issue 5 (29th September 2016) - Gallego, Samuel V.; Perez-Mato, J. Manuel; Elcoro, Luis; Tasci, Emre S.; Hanson, Robert M.; Momma, Koichi; Aroyo, Mois I.; Madariaga, Gotzon
Abstract : A free web page under the name MAGNDATA, which provides detailed quantitative information on more than 400 published magnetic structures, has been developed. This first article is devoted to explaining the information and analysis tools available there for a set of more than 360 commensurate magnetic structures. Abstract : A free web page under the name MAGNDATA, which provides detailed quantitative information on more than 400 published magnetic structures, has been developed and is available at the Bilbao Crystallographic Server (http://www.cryst.ehu.es ). It includes both commensurate and incommensurate structures. This first article is devoted to explaining the information available on commensurate magnetic structures. Each magnetic structure is described using magnetic symmetry, i.e. a magnetic space group (or Shubnikov group). This ensures a robust and unambiguous description of both atomic positions and magnetic moments within a common unique formalism. A non‐standard setting of the magnetic space group is often used in order to keep the origin and unit‐cell orientation of the paramagnetic phase, but a description in any desired setting is possible. Domain‐related equivalent structures can also be downloaded. For each structure its magnetic point group is given, and the resulting constraints on any macroscopic tensor property of interest can be consulted. Any entry can be retrieved as a magCIF file, a file format under development by the International Union of Crystallography. An online visualization tool using Jmol is available, and the latest versions of VESTA and Jmol support the magCIF format, such that these programs can be used locally for visualization and analysis of any of the entries in the collection. The fact that magnetic structures are often reported without identifying their symmetry and/or with ambiguous information has in many cases forced a reinterpretation and transformation of the published data. Most of the structures in the collection possess a maximal magnetic symmetry within the constraints imposed by the magnetic propagation vector(s). When a lower symmetry is realized, it usually corresponds to an epikernel (isotropy subgroup) of one irreducible representation of the space group of the parent phase. Various examples of the structures present in this collection are discussed.